The Mediating Role of Brand Image on the Influence of Digital Marketing and Word of Mouth on Property Purchase Intention in Bali - ISWARA, A.A Ngurah KT Pradnyana; INDIANI, Ni Luh Putu; WAHYUNI, Ni Made (International Journal of Environmental, Sustainability, and Social Science, 2024)
The growing property industry in Indonesia is a very promising opportunity for property business people, especially in Bali. But in offering property products today a new problem arises where the ability of marketers to spearhead in offering their products. This study aims to analyse the effect of digital marketing and word of mouth on purchase intention with brand image as a mediator. The object of this research is the property industry in Bali Province. The sample in this study were 100 respondents at least 25 years old, using online media to find information about property, and having plans to buy property in Bali. The data collection method is a survey method with a questionnaire. The analysis technique used is inferential analysis technique with Partial Least Square (PLS). The results found that digital marketing and word of mouth have a significant positive effect on purchase intention. In addition, brand image is proven to be able to mediate the influence of digital marketing and word of mouth on purchase intention. This proves the theory of planned behaviour that consumer intentions are based on trust in information obtained through online media or directly from someone who is considered credible. Property agent marketers in Bali are expected to take advantage of digital marketing by advertising to make it easier for consumers to remember property agents so as to attract more potential customers.